A Meta-Analysis on Randomised Controlled Clinical Trials Evaluating the Effect of the Dietary Supplement Chitosan on Weight Loss, Lipid Parameters and Blood Pressure - Moraru, Cristina; Mincea, Manuela Maria; Frandes, Mirela; Timar, Bogdan; Ostafe, Vasile (Medicina (Kaunas, Lithuania), 2018)
Background and objectives: Erratic results have been published concerning the influence of the dietary supplement chitosan used as a complementary remedy to decrease the body weight of overweight and obese people. The published articles mention as secondary possible benefits of usage of chitosan the improvement of blood pressure and serum lipids status. We performed a meta-analysis evaluating body weight, body mass index, total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol, triglycerides, systolic and diastolic blood pressure among overweight and obese patients. Materials and Methods: Searching MEDLINE, Cochrane up to December 2017 on clinical trials that have assessed the influence of chitosan used as a dietary supplement on overweight and obese patients. An additional study was identified in the References section of another meta-analysis. A total of 14 randomised control trials (RCT) were used to assess the effect on body weight, serum lipids and blood pressure. Results: The usage of chitosan as a dietary supplement up to 52 weeks seems to slightly reduce the body weight (−1.01 kg, 95% CI: −1.67 to −0.34). Considering the other parameters studied, the most significant improvement was observed in systolic and diastolic blood pressure: −2.68 mm Hg (95% CI: −4.19 to −1.18) and −2.14 mm Hg (95% CI: −4.14 to −0.14) in favour of chitosan versus a placebo. Conclusions: Based on the meta-analysis realized with 14 RCT we concluded that the usage of chitosan as a dietary supplement can lead to a slight short- and medium-term effect on weight loss and to the improvement of serum lipid profile and cardiovascular factors.